2020
DOI: 10.1016/j.jaac.2019.06.018
|View full text |Cite
|
Sign up to set email alerts
|

The Centrality of Doubting and Checking in the Network Structure of Obsessive-Compulsive Symptom Dimensions in Youth

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 48 publications
3
14
0
1
Order By: Relevance
“…Other results showed that higher anxious features related to higher obsessing features support the relation between anxiety and OC features in community samples, particularly mental aspects of OCD, i.e., mental compulsions [66]. This result may be viewed consistent with the notion that mental compulsions are overlapped with generalized anxiety and worry in youth [67].…”
Section: Discussionsupporting
confidence: 66%
“…Other results showed that higher anxious features related to higher obsessing features support the relation between anxiety and OC features in community samples, particularly mental aspects of OCD, i.e., mental compulsions [66]. This result may be viewed consistent with the notion that mental compulsions are overlapped with generalized anxiety and worry in youth [67].…”
Section: Discussionsupporting
confidence: 66%
“…Substantial research connects IU with obsessive-compulsive disorder (OCD), generalized anxiety disorder (GAD), and social anxiety disorder (SAD) due to its relationship with worrying and catastrophizing. Doubt and IU are seen as core features of OCD (Gillett et al, 2018;Cervin et al, 2020). Gillett and colleagues (2018) claimed that compulsions such as checking behaviors could be seen as attempts to reduce uncertainty or ambiguity.…”
Section: Pathways From Iu To Various Forms Of Child Psychopathologymentioning
confidence: 99%
“…The checklist is followed by a clinician-led interview assessing symptom severity across six theoretically derived dimensions (aggressive, religious/ sexual, symmetry, contamination, hoarding, and miscellaneous symptoms) and of overall OCD severity. The DY-BOCS has sound psychometric properties and good construct validity in youth [see summary in Cervin et al (2019aCervin et al ( , 2019b] and adult samples (Pertusa, Fernandez de la Cruz, Alonso, Menchon, & Mataix-Cols, 2012;Rosario-Campos et al 2006), but the factor structure of its symptom checklist has never been investigated (Rosario-Campos et al, 2006).…”
Section: Dy-bocsmentioning
confidence: 99%